Commencement May, 1987 - (:unkn) unknown (My University, 1987)
Programs for commencement, honors day and other related campus events. Also included are addresses to graduating classes; scholarship information; programs for alumni, faculty, senior banquets and senior class plays; and graduation invitations. The materials contained in this series provide documentation of speakers, music, and order of events at commencement and related functions. In addition, this collection includes lists of graduates and the degrees they received.
UWRF Series 27
Keywords: Commencement; Graduation; Ceremonies